Vernacular architecture in old Malay building through Malay historiography - Jaffar, Siti Rabiatul Adawiah; Sujud, Arba'ie; Noor Muhammad, Salmah Jan (Human Resource Management Academic Research Society, 2020)
Vernacular is said to be derived from the Latin term vernaculus which means domestic or local which means 'place'. However, in this context, the vernacular traditions clearly emphasize the conditions, local materials, environment and behavior as well as local customs that focus on traditional Malay society. This is reflected in the architecture that can be studied with the senses dependent on the thoughts and views of the community. Among them is the architecture of old Malay building. Research vernacular aspect of old Malay architecture displays a close link exists or affinity with nature and the community trust, which is the main source of living of the people. In fact, the nature and confidence in ensuring the community's ability to meet the objectives of old Malay income, as a protective domain, not only of the current situation, even include descriptions of culture. In this case, the old Malay architecture have been identified in the text of the Malay historiography, historical documentation as the material of the Malays. Hence, to highlight the description of the vernacular architecture of the old Malay, research will be conducted on the texts, intended to show the relationship of the Malay community with nature and belief, thus explaining its ability to meet the objectives of the production building old Malay, include their role as protectors of the current situation and highlights the value of Malay culture.